Failure analysis of plates with singular and non-singular stress raisers by a coupled peridynamic model. (July 2019) - Zhang, Heng; Qiao, Pizhong; Lu, Linjun
Highlights: A new numerical technique for whole failure progress analysis of notched plates by the coupled peridynamic criterion (CPC). Concurrent consideration of both the stress and energy conditions. The well predicted successive failure progress by the CPC model. Abstract: A new numerical technique for whole failure progress analysis of notched plates is presented with the coupled peridynamic criterion (CPC) model, in which both the stress and energy conditions are concurrently considered. In this model, the CPC parameter of finite crack length is obtained numerically in peridynamics, and it is then applied in the whole failure progress prediction of notched plate. The proposed technique is used to analyze the elastic and failure behaviors of plates with non-singular (elliptical hole) and singular (center-crack) concentrations, and it is compared with the available analytical and experimental data. The results show that the proposed CPC model can better capture the critical load of notched plates than the existing bond failure criterion, especially for the short crack and non-singular hole cases. The successive failure progress, from the intact phase to the crack initiation and propagation, is well predicted by the present CPC model.